Role of Crisis Management in Construction Projects - J, Rajprasad; V, Thamilarasu; N, Mageshwari (International Journal of Engineering and Technology, 2018)
Crisis management is the method which is formed by the organization to overcome the crisis. Crisis management is important, which helps in the completion of the construction project on time. It gives a theory of how to manage the crisis management with the factors which leads to crisis in the construction project. However, only when the work flow continues without any interruption even during crisis that crisis management method is effective. For forming an effective crisis management technique, the probability of crisis in construction projects must be identified as each factor have their unique effects. Depending upon major factors like technical, labour, organizational, material, time, equipment, communication, financial and other factors which are responsible for the cause of crisis in projects are considered. The research is carried out through questionnaire survey analysis made among the various project managers from different construction project site.Â